Shift in fungal communities associated with Pinus sylvestris stands affected by root rot - Davydenko , K. V.; Ustsky, I. M. (Forestry and Forest Melioration, 2023)
Introduction Scots pine (Pinus sylvestris) covers large areas in European regions with significant economic importance to Ukrainian forest industry. Root rot caused by the wood-decay fungus Heterobasidion annosum damages both below- and above-ground parts of Scots pines. The disease progress is likely to be affected by reshaping in the forest such as soil properties, vegetation composition, and tree age. These changes are apparently followed up by paralleled shifts in fungal community composition on forest soil with potential feedback on ecosystem functioning. The objective of the study was to screen fungal groups associated with the root system of P. sylvestris in stands affected by H.annosum s.s. to better understand the pathogenesis and development of root rot infection, as well as to recognize whether root size and disease severity affect diversity of fungi of the root system in the forest-steppe conditions of Ukraine. The additional object was to study other resident microflora of P. sylvestris root infested by H.annosum s.s. to find out whether the H. annosum s.s. impacts the overall diversity of other fungi. Materials and Methods The field study was carried out in 2018–2020. Field study sites were pure pine forest stands located in Kharkiv region (compartment 126, subcompartment 7, tract Bugri, Kharkiv Forest Research Station). Wood core and root samples from P. sylvestris were collected from the five infected (50–100 m apart from each other) and five non-infected trees (up to 500 m apart from the infested area and 50–100 m apart from each other). Wood and root samples were used for fungal culturing and direct sequencing using ITS1F and ITS4 primers. Results In the present study, we tried to evaluate fungal communities across diseased Pinus sylvestris stands and investigated correlations between taxonomic composition and forest health. Not surprisingly, root rot infestation had a significant effect on root-associated fungal abundance and diversity. During disease development, the root-associated fungal community shifted in composition from dominance by saprotrophic fungi to ectomycorrhizal and pathogenic fungal species. Our results suggested that maintenance of functional diversity in the root-associated fungal community may sustain long-term forest health or even root rot resistance to some extent by retaining a capacity for symbiosis-driven recycling of organic nutrients; however, this hypothesis is necessary to carefully examine and prove further. Conclusions Fungal culturing from 10 surface-sterilized wood cores resulted in 21 fungal cultures, 2.1 per wood segment. Direct sequencing from 40 surface-sterilized segments of lateral roots resulted in 247 fungal sequences or 6.2 per root segment on average. The most dominant fungi from the infested trees of Pinus sylvestris were Dactylonectria macrodidyma (4.98%), Acremonium sp (4.52%), Cladosporium cladosporioides (4.07%) from Ascomycota and Heterobasidion annosum s.s. (4.07%) from Basidiomycota, while for non-infested group Unidentified Ascomycota175244 (13.19%), Penicillium spinulosum (9.89%), Acremonium sp. (8.79%), Bionectriaceae sp. (8.79%) were the most common. 2 Figs., 2 Tables, 32 Refs.